The clinical effect of hippotherapy on gross motor function of children with Cerebral Palsy - K Litlle (South African Journal of Physiotherapy, 2013)
Background: Cerebral palsy (CP) is the most common cause of physical disability affecting gross motor function (GMF ) in early childhood. Hippotherapy is a treatment approach aimed at improving GMF in children with CP. Several systematic reviews have been published showing an improvement in Dimension E of the Gross Motor Function Measure (GMFM ) after hippotherapy. However, these reviews failed to evaluate the clinical effect of hippotherapy in improving GMF in children with CP.